2016
DOI: 10.4274/tjh.2015.0368
|View full text |Cite
|
Sign up to set email alerts
|

Results of Four-Year Rectal Vancomycin-Resistant Enterococci Surveillance in a Pediatric Hematology-Oncology Ward: From Colonization to Infection

Abstract: Objective:To investigate the clinical impact of vancomycin-resistant enterococci (VRE) colonization in patients with hematologic malignancies and associated risk factors.Materials and Methods:Patients colonized and infected with VRE were identified from an institutional surveillance database between January 2010 and December 2013. A retrospective case-control study was performed to identify the risk factors associated with development of VRE infection in VRE-colonized patients.Results:Fecal VRE colonization wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Regarding possible differences between VREfm-colonised and VREfm-infected patients, the presence of a temporary artificial stoma, a recent surgical procedure, previous treatment with carbapenems, preceding chemotherapy and underlying haemato-oncological disease were significantly associated with the development of clinical symptoms. These findings are in line with current studies, identifying preterm babies as well as immunosuppressed paediatric intensive care patients—in particular children with a haematological/oncological diagnosis—as a high-risk population for VREfm-C and VREfm-I [ 19 , 20 , 35 , 64 67 ]. High exposure to antibiotics, especially third-generation cephalosporins, seems to further increase the risk [ 19 , 35 , 68 ].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding possible differences between VREfm-colonised and VREfm-infected patients, the presence of a temporary artificial stoma, a recent surgical procedure, previous treatment with carbapenems, preceding chemotherapy and underlying haemato-oncological disease were significantly associated with the development of clinical symptoms. These findings are in line with current studies, identifying preterm babies as well as immunosuppressed paediatric intensive care patients—in particular children with a haematological/oncological diagnosis—as a high-risk population for VREfm-C and VREfm-I [ 19 , 20 , 35 , 64 67 ]. High exposure to antibiotics, especially third-generation cephalosporins, seems to further increase the risk [ 19 , 35 , 68 ].…”
Section: Discussionsupporting
confidence: 91%
“…in hospitalized children. Unfortunately, in recent decades there has been an increase in vancomycin‐resistant enterococci (VRE) in pediatric patients, which has a severe impact on children . This is a significant problem at Children's Hospital of Nanjing Medical University, and efficient and selective antibiotic treatment should be initiated for isolated Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in recent decades there has been an increase in vancomycin-resistant enterococci (VRE) in pediatric patients, which has a severe impact on children. 16 This is a significant problem at Children's Hospital of Nanjing Medical University, and efficient and selective antibiotic treatment should be initiated for isolated Enterococcus spp. With regard to E. coli, which was the second most common isolated pathogen in the present study, two common and cheap antibiotics (amikacin and piperacillin/tazobactam) were found to be highly effective and are recommended for use.…”
Section: Discussionmentioning
confidence: 99%
“…Also studied were three non-fermenters with 5/144 (3%) studies about Acinetobacter baumannii [82,140–143], 4/144 (3%) studies about Pseudomonas aeruginosa [83,84,144,145], and 5/144 (3%) studies about Stenotrophomonas maltophilia [8588,146], often specified as either multidrug- or extensively drug-resistant. We also found several studies focusing on four well-known healthcare-associated bacteria, with 11/144 (8%) focusing on VRE [8998,147,148], 7/144 (5%) focusing on carbapenemase-producing K. pneumoniae (KPC) [99102,149151], 2/144 (1%) focusing on methicillin-resistant Staphylococcus aureus (MRSA) [42,152], and 6/144 (4%) focusing on extended-spectrum beta-lactamase-producing Escherichia coli (ESBL-E) [103,104,153–156]. We also found that fungi typically resistant to antifungals were studied, 3/144 (2%) studies about Aspergillus spp.…”
Section: Resultsmentioning
confidence: 74%